Impact of Education Level, Training and Experience on Auditor's Professional Skepticism - Fathorrahman, Fathorrahman; Subhan, Subhan; Wahyuni, Ummi (University Muhammadiyah Aceh, 2025)
Abstract This study aims to analyze the effect of education level, training and experience on auditor skepticism. This study was conducted at the Sampang Regency Inspectorate. This study uses primary data through the distribution of questionnaires to 30 employees of the Sampang Regency Inspectorate. The results of the study indicate that the level of education does not affect the professional skepticism of the examiner, this can be shown based on the probability of the education level variable, which is 0.0940.05. Training does not affect the professional skepticism of the examiner, this can be shown based on the probability of the training variable, which is 0.5820.05. Experience affects the professional skepticism of the examiner, this can be shown based on the probability of the experience variable 0.0210.05. Thus, the level of education and training does not affect the professional skepticism of the examiner, while experience affects the professional skepticism of the examiner